2016
DOI: 10.1038/srep24168
|View full text |Cite
|
Sign up to set email alerts
|

Early-onset obesity dysregulates pulmonary adipocytokine/insulin signaling and induces asthma-like disease in mice

Abstract: Childhood obesity is a risk factor for asthma, but the molecular mechanisms linking both remain elusive. Since obesity leads to chronic low-grade inflammation and affects metabolic signaling we hypothesized that postnatal hyperalimentation (pHA) induced by maternal high-fat-diet during lactation leads to early-onset obesity and dysregulates pulmonary adipocytokine/insulin signaling, resulting in metabolic programming of asthma-like disease in adult mice. Offspring with pHA showed at postnatal day 21 (P21): (1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 58 publications
4
40
2
Order By: Relevance
“…Our results are comparable to a recent model of murine pre and postnatal hyperalimentation showing increased AHR without alteration in bronchial structure that may be due in part increased T h 17 cells (Dinger et al. ).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our results are comparable to a recent model of murine pre and postnatal hyperalimentation showing increased AHR without alteration in bronchial structure that may be due in part increased T h 17 cells (Dinger et al. ).…”
Section: Discussionsupporting
confidence: 89%
“…Our results show increased AHR in HFD offspring that continued on HFD compared to offspring fed HFD at weaning. Our results are comparable to a recent model of murine pre and postnatal hyperalimentation showing increased AHR without alteration in bronchial structure that may be due in part increased T h 17 cells (Dinger et al 2016).…”
Section: Discussionsupporting
confidence: 88%
“…Previous studies related to obesity‐associated asthma suggest that AHR develops as a result of adipokine‐induced dysregulation of airway contractility, lung fibrosis, changes in collagen and elastin expression, and non‐Th2 inflammation . In contrast, we found that short‐term HFD feeding–induced metabolic alterations in OVA‐driven experimental allergic asthma are associated with protection from AHR development, pulmonary inflammation, altered DC activity and decreased Th1/Th17 differentiation.…”
Section: Discussioncontrasting
confidence: 67%
“…In accordance with those findings, it was also described that non-allergen-sensitized mice and rats born to mothers exposed to HFD during pregnancy and lactation spontaneously develop lower respiratory system compliance and higher respiratory system resistance [18,19]. Similar data were found in adult non-allergen-sensitized offspring of mice breastfed by dams consuming HFD [20].…”
Section: Introductionsupporting
confidence: 79%